A first‐in‐class, first‐in‐human, phase I trial of CIGB‐552, a synthetic peptide targeting COMMD1 to inhibit the oncogenic activity of NF‐κB in patients with advanced solid tumors. Issue 6 (27th May 2021) - Vallespi, Maribel G.; Mestre, Braulio; Marrero, Maria A.; Uranga, Rolando; Rey, Diana; Lugiollo, Martha; Betancourt, Mircea; Silva, Kirenia; Corrales, Danay; Lamadrid, Yanet; Rodriguez, Yamilka; Maceo, Anaelys; et al.
Abstract: CIGB‐552 is a synthetic peptide that interacts with COMMD1 and upregulates its protein levels. The objectives of this phase I study were safety, pharmacokinetic profile, evaluation of the lymphocytes CD4+ and CD8+ and preliminary activity in patients with advanced tumors. A 3 + 3 dose‐escalation design with seven dose levels was implemented. Patients were included until a grade 3 related adverse event occurred and the maximum tolerated dose was reached. The patients received subcutaneous administration of CIGB‐552 three times per week for 2 weeks. Single‐dose plasma pharmacokinetics was characterized at two dose levels, and tumor responses were classified by RECIST 1.1. Twenty‐four patients received CIGB‐552. Dose‐limiting toxicity was associated with a transient grade 3 pruritic maculopapular rash at a dose of 7.0 mg. The maximum tolerated dose was defined as 4.7 mg. Ten patients were assessable for immunological status. Seven patients had significant changes in the ratio CD4/CD8 in response to CIGB‐552 treatment; three patients did not modify the immunological status. Stable disease was observed in five patients, including two metastatic soft sarcomas. We conclude that CIGB‐552 at dose 4.7 mg was well tolerated with no significant adverse events and appeared to provide some clinical benefits.